Correlation between the levels of potassium and polyamines in the leaves of grapevine - Miklós, Erzsébet; Sarjala, Tytti (Acta Biologica Szegediensis, 2002)
Potassium and the most abundant polyamines (putrescine, spermidine and spermine) concentrations were determined in the leaf blades of Vitis vinifera L. cv. White Riesling, Ezerjó , Kövidinka, Chardonnay, Cabernet Sauvignon , Merlot, Kadarka varieties at ripening to characterize the correlation between these two types of osmolytes under drought stress and low nutrient supply. K+ concentration in the leaf blades changed in the range of 0.27-0.81% , indicating serious K+ deficiency . Kadarka and Ezerjó varieties accumulated the lowest and Kövidinka the greatest quantity of potassium. Below 0.5% K+ content the increase of free and soluble-conjugated putrescine concentration could be observed. The highest levels were formed in the leaves of Ezerjó: 1785 nmol/g fw. free and 589 nmol/g fw. soluble-conjugated putrescine and these values decreased to 11 nmol/g fw. and 14 nmol/g fw. at Kövidinka variety. Free spermidine concentration changed in the range of 25-100 nmol/g fw and the content of conjugated form was lower. The free and soluble-conjugated spermime levels remained below 20 nmol/g fw. Accumulation of spermidine and spermine didnot correlate with the K+ concentration in the leaf blades.